Acesso aos antipsicóticos atípicos para o tratamento de esquizofrenia no SUS: impacto orçamentário e gestão de riscos como ferramentas para orientar a alocação nos componentes da assistência farmacêutica. - Lucas Reis Felício (2024)
Schizophrenia is a severe and chronic psychiatric disorder with significant social and economic consequences, treated with antipsychotic medications. Antipsychotics are classified into typical and atypical categories, with similar efficacy but differing adverse effects. Typical antipsychotics are associated with a higher risk of developing extrapyramidal symptoms, higher treatment discontinuation rates, and increased risks of rehospitalization. In contrast, atypical antipsychotics have better tolerability and are lower discontinuation rates. Major therapeutic guidelines, including those in Brazil, recommend that the choice of antipsychotic be based on an individualized assessment of the patient's context, without a preferential order. The Brazilian Unified Health System (SUS) provides both typical and atypical antipsychotics, with significant differences in access and funding. Typical antipsychotics are available through the Primary Health Care network, funded by the Basic Component of Pharmaceutical Assistance (CBAF), whereas atypical antipsychotics are centrally managed through the Specialized Component of Pharmaceutical Assistance (CEAF) by state governments. Consequently, transferring atypical antipsychotics from CEAF to CBAF could facilitate access, but would also have financial and organizational implications. This study aims to investigate access to atypical antipsychotics in CBAF as a strategy to enhance access, through a risk management analysis and a budget impact analysis (BIA). The risk management analysis systematically identified and evaluated 20 risk events for each component, detailing their consequences and proposing mitigation measures. Both components exhibited strengths and weaknesses, and changes in access flows require evaluation and monitoring by local managers. The BIA explored different scenarios and migration proposals, demonstrating that, in the context of schizophrenia, the transfer between components could either generate savings or incur significant financial consequences, depending on the assumptions used in the model. The results indicate that changes in the access flow of atypical antipsychotics between Pharmaceutical Assistance components should be carefully evaluated by managers and decision-makers, as the analysis revealed both positive and negative consequences for management and financing.